Computational Intelligence in Information Systems Proceedings of the Computational Intelligence in Information Systems Conference (CIIS 2018) - Omar, Saiful; Haji Suhaili, Wida Susanty; Phon-Amnuaisuk, Somnuk; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book constitutes the Proceeding of the Computational Intelligence in Information Systems conference (CIIS 2018), held in Brunei, November 16 - 18, 2018. The CIIS conference provides a platform for researchers to exchange the latest ideas and to present new research advances in general areas related to computational intelligence and its application. The 19 revised papers presented in this book have been carefully selected from 41 submissions. The Conference contributes to major fields of the Computing and Information Systems in theoretical and practical aspects. This include Computational Intelligence Techniques, Data Mining, Big Data, the Internet of Things (IoTs), Machine Learning, Predictive Analytics, Product and Design technology, Smart Products, Human Centered Design (HCD), Additive Manufacturing, Information Security, Computer Networks and Cyber Technologies. .
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence